2008
DOI: 10.1128/aem.01455-08
|View full text |Cite
|
Sign up to set email alerts
|

Formate-Dependent H 2 Production by the Mesophilic Methanogen Methanococcus maripaludis

Abstract: Fdh1 isozyme, indicating that it was the primary Fdh. In contrast, a mutant containing a deletion of the gene encoding the Fdh2 isozyme possessed near-wild-type activities, indicating that this isozyme did not play a major role. H 2 production by a mutant containing a deletion of the coenzyme F 420 -reducing hydrogenase Fru was also severely reduced, suggesting that the major pathway of H 2 production comprised Fdh1 and Fru. Because a ⌬fru-⌬frc mutant retained 10% of the wild-type activity, an additional pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 38 publications
4
92
0
Order By: Relevance
“…Indeed, experiments with cell suspensions have already shown that rates of methanogenesis can substantially exceed rates of H 2 production from formate (5). As a further test, our approach here was to genetically remove formate-hydrogen lyase activity, so that H 2 would not be produced from formate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, experiments with cell suspensions have already shown that rates of methanogenesis can substantially exceed rates of H 2 production from formate (5). As a further test, our approach here was to genetically remove formate-hydrogen lyase activity, so that H 2 would not be produced from formate.…”
Section: Resultsmentioning
confidence: 99%
“…In the conventional view, during growth on formate, H 2 generated from formate serves as the electron donor. Indeed, H 2 is generated from formate and recycled in a poorly understood manner (5,11). However, if there is no direct requirement for H 2 in methanogenesis (5, 7), most of the hydrogenases encoded in the genome ought to be dispensable during growth on formate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Frc enzyme shows similar activities of F420 reduction from H 2 or H 2 production from reduced F420 [36] . The latter activity is important, for example, during growth on formate [37] . [39] .…”
Section: Activitymentioning
confidence: 99%
“…These microorganisms contain very high levels of different types of hydrogenases and consume H 2 at very high rates. Furthermore, under certain conditions the H 2 uptake system can be induced to produce H 2 at elevated proportions by using formate as an electron donor Lupa et al 2008;Costa et al 2013a). Certain species of methanogens can produce H 2 by fixing nitrogen, and therefore have the potential to produce H 2 using the nitrogenase system.…”
mentioning
confidence: 99%